Difference between revisions of "Stewart's Theorem"
Happyhuman (talk | contribs) (→Proof) |
Happyhuman (talk | contribs) (→Proof) |
||
Line 17: | Line 17: | ||
<math>m+n = a</math> so | <math>m+n = a</math> so | ||
*<math>m^2n + n^2m = (m + n)mn = amn</math> and | *<math>m^2n + n^2m = (m + n)mn = amn</math> and | ||
− | + | <cmath>d^2m + d^2n = d^2(m + n) = d^2a</cmath> | |
− | |||
This simplifies our equation to yield <math>c^2n + b^2m = amn + d^2a,</math> or Stewart's Theorem. | This simplifies our equation to yield <math>c^2n + b^2m = amn + d^2a,</math> or Stewart's Theorem. | ||
Revision as of 15:27, 7 January 2020
Statement
Given a triangle with sides of length
opposite vertices are
,
,
, respectively. If cevian
is drawn so that
,
and
, we have that
. (This is also often written
, a form which invites mnemonic memorization, i.e. "A man and his dad put a bomb in the sink.")
![Stewart's theorem.png](https://wiki-images.artofproblemsolving.com//b/b3/Stewart%27s_theorem.png)
Proof
Applying the Law of Cosines in triangle at angle
and in triangle
at angle
, we get the equations
Because angles and
are supplementary,
. We can therefore solve both equations for the cosine term. Using the trigonometric identity
gives us
Setting the two left-hand sides equal and clearing denominators, we arrive at the equation: .
However,
so
and
This simplifies our equation to yield
or Stewart's Theorem.